Fireside corrosion study of superheater materials in advanced power plants - Syed, Adnan U. (Cranfield University, 2011)
Conventional power plants are major emitters of CO2 gases, which are believed to be contributing to global warming. An efficient, co-firing biomass-coal power plant with oxy-firing combustion system (running at high steam temperature and pressure), can play a vital role in CO2 emission reduction. However, these techniques will further worsen the issue of fireside corrosion of heat exchangers. An increase in fireside corrosion rates can cause short component lives and unexpected failures if not dealt with appropriately. The aim of this PhD study was to use laboratory-based testing to assess the performance of alloy materials under superheater conditions in simulated co-fired (biomass and coal) air and oxy-fired combustion. In this PhD project five different alloys were used. Synthetic deposits were also prepared to simulate superheater deposit compositions. Tests were carried out at temperatures appropriate for metal temperatures in superheaters/reheaters of future power plants. The performance of samples was determined using: mass change data, advanced microscopy techniques, x-ray diffraction and dimensional metrology. Additional tests were carried out to investigate deposit stability and the effect of high concentrations of salts. The results achieved have confirmed the hypothesis that increased fireside corrosion rates are due to the combined effect of extreme environment: high temperatures, SO2 and HCl gases, aggressive deposits. Corrosion damage follows trends that resembles ‘bell-shaped’ curve in both air and oxy-fired conditions. Alloy corrosion damage in novel oxy-firing compared to air-firing conditions was significantly higher at 700C. The peak of the curve shifts from 650 to 700C in oxy-fired conditions. The alloys with higher chromium content clearly showed better corrosion resistance. The work on deposit chemistry and exposure to high salt concentrations has improved the understanding of corrosion reaction mechanisms. Corrosion damage data have been used to produce basic fireside corrosion mathematical model; which can be used as a stepping stone towards further development of fireside corrosion models.